COVID-19 and global poverty and food security - Vos, Rob; McDermott, John; Swinnen, Johan (Annual Reviews, 2022)
The impacts of coronavirus disease 2019 (COVID-19) on food systems, poverty, and nutrition have been caused by generalized economic recession and disruptions in agrifood supply chains. This article reviews a growing empirical literature assessing those impacts. The review confirms that income shocks and supply disruptions have affected food security and livelihoods more where supply chains were poorly integrated and poverty where market informality had a greater presence before COVID-19. Yet, as the pandemic persists, outcomes remain uncertain and reliable data are still sparsely available. This review also reveals how methodological approaches have evolved during the pandemic, ranging from model-based scenario analyses, telephone survey evidence, case-study analyses, and data collection on policy responses and their effects. This review concludes that while we have good insight into the COVID-19 pandemic's impacts on food security, there is still much that we do not know, requiring much more rigorous hypothesis testing based on reliable and observed data.